Assessment of the Implementation of RTE Act, 2009, in Context of Curriculum in Government and Private Elementary Schools of western Uttar Pradesh - Sharma, Mudita; Shafeeq, Nikhat Yasmin (JOURNAL OF INDIAN EDUCATION, 2020)
The present paper seeks to find out the status of the implementation of Right to Education (RTE) Act-2009, in the elementary schools of western Uttar Pradesh in the light of the norms prescribed in the RTE Act in context of curriculum. The Act was passed in 2009 and came into force since 1st April, 2010. About ten years of the implementation of the Act, researchers attempted to find out the status of its implementation according to the provisions of curriculum. A selfmade tool was used by the researchers to assess the implementation of the RTE Act. Both quantitative and qualitative analysis was performed. Coding, scoring of the data and analysis was done by using the SPSS software. The statistical techniques used for analysing the data were: percentage, t-test and graphs. It was found that some of the provisions of the RTE Act in context of curriculum are followed in the elementary schools of western U.P.